Panstrongylus guentheri Berg, 1879 (Hemiptera, Reduviidae, Triatominae): first record in Mato Grosso, Brazil - Mirian Francisca Martins; Sinara Cristina de Moraes; Sirlei Franck Thies; Veruska Nogueira de Brito; Rodrigo Gurgel-Gonçalves; Cleber Galvão (Revista da Sociedade Brasileira de Medicina Tropical)
ABSTRACT Background: This paper reports the occurrence of Panstrongylus guentheri Berg, 1879 in the State of Mato Grosso (MT). Methods: Triatomines were captured in rural environments in municipalities of MT. Specimens were identified, and Trypanosoma cruzi infection was investigated. Results: Nineteen specimens of Panstrongylus guentheri were found, primarily inside houses. The geographical distribution of this species was recorded in nine municipalities of Mato Grosso, and parasitological tests did not detect T. cruzi on P. guentheri. Conclusions: The distribution of this species in Brazil has been recently updated.